Profile of blood donors in a hemotherapy institution in Midwestern Brazil - Weldson Ferreira Abreu; Leticia Aparecida Silva; Polyanna Campos Gonçalves Sousa (Hospital de Clínicas de Itajubá, 2022)
Objective: To describe the profile of blood donors in a hospital in the Midwest of Brazil with its own blood bank to have a diagnostic view of the establishment and enable the planning of improvements in services. Methods: This is a descriptive, retrospective study with a quantitative approach. A proportional stratified sampling technique was used, with a confidence level of 95% and a margin of error of 5%, to represent and characterize the study population, obtaining a sample of 363 donors. Subsequently, a proportional allocation was performed in the established groups (fit donors, unfit donors, and platelet apheresis donors). Results: The profile of eligible donors in the institution studied was composed of married (55.2%), male (63.7%), aged between 20 and 30 years (40.4%), with O RhD+ blood (46.7%) and A RhD+ (29.6%) more prevalent. Apheresis platelet donors (50%) are single, female (81.3%), and aged between 31 and 40 years (43.8%). As for unfit donors, 94.8% are temporary-unfit donors, married donors (53.2%), female (54.5%), and between 20 and 40 years old (54.6%), with the categories of health condition and lifestyle being the most prevalent reasons for disability. Conclusion: There is a hegemony for replacement and first-time donors, showing the effectiveness of the solidarity policy implemented in the institution, but it shows the low effectiveness in the loyalty of these donors.